Evaluation of the dairy sustainability assessment tool (DSAT) for dairy systems in East Africa - Augustine A. Ayantunde; Asaah Ndambi; Aart van der Linden; Adolfo A. Aranguiz; Hassan Pishgar Komleh; Jan van der Lee (International Journal of Agricultural Sustainability)
Sustainability assessment of dairy systems is necessary to understand bottlenecks and to identify measures to enhance sustainability of the systems. The Dairy Sustainability Assessment Tool (DSAT) was developed with a focus on the facilitation of discussion on sustainability among dairy sector actors in East Africa. DSAT has been applied in several case studies, but the tool has not been systematically evaluated. The objectives of this study were to evaluate the strengths and weaknesses of DSAT and to compare its main features with similar dairy assessment tools for Africa. This evaluation consisted of a literature search to identify relevant assessment tools and an online survey about the tool among its users. DSAT was different from other tools compared with as it does not require input data from farm surveys as the assessments rely on expert opinion, and it can conduct assessments at farm, regional and national scales. Results also showed that DSAT was appropriate for holistic assessments of the sustainability of dairy systems in Africa by providing a good overview of threats to sustainability. Weaknesses were mainly the scoring of indicators, which tends to be subjective and the absence of numerical reference values for indicators. Therefore, improving DSAT requires addressing the identified weaknesses.